Relay cropping of cucurbits in furrows under bed planted wheat for higher profitability - Tripathi, Subhash Chandra; Meena, Raj Pal; Chander, Subhash (Journal of Cereal Research, 2021)
A field experiment was condcuted for four consecutive seasonsfrom 2016-17 to 2019-20 at ICAR- Indian Institute of Wheat andBarley Research, Karnal, Haryana with an objective to increasethe profitability through relay crops of cucurbits under bed plantedwheat crop. Eight relay crops namely musk melon, water melon,bottle guard, ridge guard, bitter guard, cucumber (kheera), cucumber(tarkakari) were planted under bed planting system with wheat. All thecucurbits were relayed in furrows at milk stage of wheat. Combinedover four years analysis revealed that wheat + bottle guard producedmaximum and signifiantly higher wheat equivalent yield (WEY), grossreturn, net return and B: C ratio, which was 80.5%, 80.5%, 227.1% and80.0% higher than sole wheat crop, respectively. Next best profitabletreatment was wheat + cucumber (tarkakari), which also produced39.8%, 112.3% and 40.0% higher WEY, net return and B: C ratio ascompared to sole wheat crop, respectively. All the relayed cucurbitswere profitable than sole wheat crop and there was no adverse effecton yield attributes and wheat yield . Thus, small and marginal farmerscan adopt this relayed cropping sytem to maximise their profit perunit time and space.